The combination of Hsp90 inhibitor 17AAG and heavy‐ion irradiation provides effective tumor control in human lung cancer cells. (13th January 2015) - Hirakawa, Hirokazu; Fujisawa, Hiroshi; Masaoka, Aya; Noguchi, Miho; Hirayama, Ryoichi; Takahashi, Momoko; Fujimori, Akira; Okayasu, Ryuichi
Abstract: Hsp90 inhibitors have become well‐studied antitumor agents for their selective property against tumors versus normal cells. The combined treatment of Hsp90 inhibitor and conventional photon radiation also showed more effective tumor growth delay than radiation alone. However, little is known regarding the combined treatment of Hsp90 inhibitor and heavy‐ion irradiation. In this study, SQ5 human lung tumor cells were used in vitro for clonogenic cell survival and in vivo for tumor growth delay measurement using a mouse xenograft model after 17‐allylamino‐17‐demethoxygeldanamycin (17AAG) pretreatment and carbon ion irradiation. Repair of DNA double strand breaks (DSBs) was also assessed along with expressions of DSB repair‐related proteins. Cell cycle analysis after the combined treatment was also performed. The combined treatment of 17AAG and carbon ions revealed a promising treatment option in both in vitro and in vivo studies. One likely cause of this effectiveness was shown to be the inhibition of homologous recombination repair by 17AAG. The more intensified G2 cell cycle delay was also associated with the combined treatment when compared with carbon ion treatment alone. Our findings indicate that the combination of Hsp90 inhibition and heavy‐ion irradiation provides a new effective therapeutic alternative for treatment of solid tumors. Abstract : The combination of Hsp90 inhibitor with heavy‐ion irradiation provided effective tumor control in vitro and in vivo with human cancer cells. This study can offer a new attractive alternative for solid tumor treatment.